The Effect of Unconditional Cash Transfer (UCT) on Household Behavior: Evidence from Iran - Heyrani, Mehrdad (Université d'Ottawa | University of Ottawa, 2020)
In 2010, in order to replace energy subsidies, Iran introduced a large Unconditional Cash transfers (UCTs) program providing monthly cash transfers per person in all households that registered for the program. This paper examines the potential effect of this program on household behavior during 2010-2011, based on the difference-in-difference method. The result shows that UCT had no significant effect on total expenditure and investment in rural and urban areas. The results also indicate that UCT has a significant effect on food nutrition security (calories and protein) in urban areas. The result of the UCT impact on fertility behavior estimates the probability of having a newborn child among urban and rural households with different family sizes. The findings of the study based on the Generalized Ordered Logit model indicate that the UCT did not lead to a significant increase in fertility behavior in urban households. However, the program negatively affected fertility behavior in households without a child, but it led to a positive impact on fertility behavior in households with one, two, and three children.